Fact-checking Technology in the Fight Against "Information Debris": Problems and Prospects - A. B. Bocharov; M. O. Demidov (Управленческое консультирование)
This article raises the question of the existence in conditions of post-truth reality, actualises the problem of blurring the distinctions between reliability and unreliability, truth and falsehood, facts and fakes, and states the imperative of the need to confront this. The aim of the work is to analyze methods / rules of fact-checking, which is a technology for determining the reliability of incoming and broadcast information. Nowadays, many disciplines,  especially the sociology of mass communications, are focused on the theoretical content of fact-checking and its set of techniques / practices. Approaches and development results of domestic and foreign researchers of mass media form the methodological basis of this article. As a result, the statement is that knowing rules of fact-checking is not only a professional competence, but an ideological setting for preferring the fact to fake, focused on consolidating the primacy of the value of truth and rejection of lies. The main conclusion is recognition of the need to supplement and consolidate professional information and communication competencies with general cultural ones.